Psychogenic Non-epileptic Seizure (PNES) Patient Profiles in Two Western Cape Epilepsy Monitoring Units and Their Utility in PNES Diagnosis - Vilyte, Gabriele Beata (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.